Advances in Stress-Wave Nondestructive Testing Methods for Evaluation of Deep Foundations - Alireza Kordjazi; Joseph T. Coe; Siavash Mahvelati (Deep Foundations Institute, 2018)
This paper introduces recent advances in stress-wave NDT systems for use in assessments of in-service foundation integrity and drilled shaft construction. The primary results of the laboratory experiments are very promising, as the acquired image was capable of differentiating changes in pile cross section as low as 0.3 cm. The preliminary results with the same hardware components on a relatively large scale cemented sand model were also promising. A brief overview is provided of both systems including hardware, survey methods, and data processing techniques, followed by a discussion on application of the results to QA/QC of deep foundations. INTRODUCTION There are two main applications in which current QA/QC NDT technology fails to provide sufficient information regarding deep foundation conditions: (1) detection of flaws in outside cover concrete of drilled shafts and corrosion in steel piling; and (2) evaluation of anomalies beneath the bottom of drilled shaft excavations. Previous studies have demonstrated the capabilities of high frequency stress waves for geotechnical and foundation evaluation purposes (Lee and Santamarina 2005; Coe and Brandenberg 2010; Coe and Brandenberg 2012; Coe and Kermani 2016). Higher frequency waves can visualize smaller anomalous features at the expense of higher attenuation and smaller propagation distance. Therefore, the goal of this study was to advance the state of NDT practice by development of a prototype high resolution stress-wave imaging system as proof-of-concept. The equipment and hardware were modular, which allowed simultaneous development of two system configurations for application to in- service foundations as well as drilled shaft excavations during construction. Results are presented based on two large scale soil models. The first laboratory model simulated section loss in an in-service steel pipe pile and drilled shaft foundation (Fig. 1a). The second model simulated anomalous conditions beneath drilled shafts excavations as might be encountered in areas with significant karst (Fig. 1b). For both models, evaluation of foundation conditions relied on the propagation of small amplitude seismic stress waves using hardware similar to those described in Coe and Brandenberg (2010) and Coe and Brandenberg (2012).